All Saints [videorecording (DVD)] - Corbett, John, 1961-; Buono, Cara; Corbin, Barry, 1940- (Sony Pictures Home Entertainment, 2017)
Based on the inspiring true story of salesman turned pastor Michael Spurlock, the tiny church he was ordered to shut down, and a group of refugees from Southeast Asia. Together, they risked everything to plant seeds for a future that might just save them all.